2010
DOI: 10.1002/lapl.201010003
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber pulsewidth tunable actively Q-switched erbium fiber laser using abrupt-tapered Mach-Zehnder block filter

Abstract: We demonstrate pulsewidth tunable Q-switched erbium fiber lasers using in-line high extinction ratio (> 30 dB) abrupt-tapered fiber Mach-Zehnder block filter and tunable Fabry-Perot filter in laser cavity. The pulsewidth can be tuning over 78 ns -23 ms. Q-switched pulse shape with pulsewidth and repetition rate at 1.84 μs, 60.84 kHz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…By incorporating an abrupt tapered MZI filter and a tunable F-P filter in laser 1 The article is published in the original. cavity, an environmental stable and pulsewidth tun able for industry applications is realized [9]. Yeh et al reported a stable and ~34 nm tunable EDF ring laser by using a tunable bandpass filter inside the EDF ring cavity [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating an abrupt tapered MZI filter and a tunable F-P filter in laser 1 The article is published in the original. cavity, an environmental stable and pulsewidth tun able for industry applications is realized [9]. Yeh et al reported a stable and ~34 nm tunable EDF ring laser by using a tunable bandpass filter inside the EDF ring cavity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Tunable filters that realize the wavelength selecting and tuning are exten sive used in the tunable fiber ring lasers, which include fiber Bragg gratings (FBGs) [2,3], Fabry-Perot (F-P) filters [4,5], filters based on multimode interference (MMI) effect [6], single mode biconic fiber taper [7], two tapered MZI [8,9], and tunable bandpass filter [10,11]. The tunable fiber lasers achieved by stretch ing a FBG axially have a tuning range of 40 nm where the fiber used to write a FBG has to experience a com plicated chemical procedure in order to enhance the mechanical strength [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, single frequency Erbium doped fiber lasers (EDFLs) have been shown to be capable of providing mode hop free lasers in the form of distributed feed back (DFB), distributed Bragg reflector (DBR) and ring lasers [8][9][10][11][12][13][14][15]. Many works have also been reported on Q switched and mode locked fiber lasers [16][17][18]. The advantage of fiber lasers is their narrow linewidth (kilohertz range), wavelength tenability, sta bility and direct compatibility with fibre networks.…”
Section: Introductionmentioning
confidence: 99%
“…The active Q-switching technique for laser pulses generation requires the use of an external modulator to obtain pulsed laser operation. In contrast to passive Q-switched lasers, when an active Q-switching technique is applied, the pulse characteristics can be modified independently of the pump power by using an electronic pulses generator, allowing the proper controlling of the laser pulses for the required laser application [14][15][16][17]. In this regard, the use of EYDCF to design active Q-switched fiber lasers has been underexploited.…”
Section: Introductionmentioning
confidence: 99%